Degradation of tetrachloroethylene by zero valent iron nanoparticles in the presence of a natural groundwater bacterial biofilm in a sandy porous media. Issue 1 (January 2021) - Crampon, Marc; Hellal, Jennifer; Mouvet, Christophe; Ollivier, Patrick
Abstract: Biofilms are naturally present in aquifers and can interact with zero valent iron nanoparticles (nZVI) used as remediation agents in contaminated groundwater; thereby they may alter nZVI reactivity towards targeted contaminants in porous media. Laboratory scale experiments using columns filled with sand (50 cm long and 5.2 cm in diameter) were performed to investigate the impact of natural biofilms on nZVI reactivity towards tetrachloroethylene (PCE) in conditions simulating an unconsolidated sandy aquifer. Solutions containing PCE were injected through the sand columns in the presence or absence of biofilm and nZVI. Concentrations in PCE and its metabolites were monitored during 45 days in dissolved and gas phases. PCE concentrations decreased at the column outlets due both to its reductive dechlorination by nZVI (~30% of injected PCE) and its sorption or deposition (as PCE-DNAPL) on sand (~35% of injected PCE). No significant differences in PCE concentrations were found in presence or absence of biofilm. However, biofilm presence affected the nature of PCE metabolites. A higher release of ethene in the column containing biofilm was observed, whereas ethane was dominant in the absence of biofilm. Microbes consumed H2 released by the corrosion of nZVI limiting the hydrogenation of ethene to ethane. The consequences of biofilm development in porous media should be taken into account when considering treatment with nZVI, as it may affect the nature of produced metabolites. Abstract : Zero-valent iron nanoparticles; Tetrachloroethylene; Biofilm; Groundwater; Reactivity.